Role of Philosophy Education for Children in Grade 3 of MINU Pucang Sidoarjo - Fabiola D. Kurnia; Winda Sulistyoningsih (JournEEL, 2019)
Philosophical education is needed for children's education. Philosophy as a value education, as well as life education that is very important for the development of human personality. Therefore, philosophical education should be given since elementary school age. The pattern of teaching philosophy applied is different from the teaching patterns of other sciences. Because in philosophy, humans are invited to think critically. In this case what is meant is that they think for themselves and find their own answers to the questions asked. However, philosophy for children should not burden the learning process. Because it must consider the local cultural context that has existed in Indonesia before. The philosophy of early childhood education seeks to uncover and examine the reality of the child's education process. The implementation of early childhood education must be based on philosophy and educational theory that are suitable for child development. Thus, the practice of education has a clear direction, goals that are relevant to the nature, needs and development of children. Children will be treated according to their situation and living conditions.